2014
DOI: 10.1021/cm403371n
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence in ZnO:Co2+ (0.01%–5%) Nanoparticles, Nanowires, Thin Films, and Single Crystals as a Function of Pressure and Temperature: Exploring Electron–Phonon Interactions

Abstract: This work investigates the electronic structure and photoluminescence properties of Co2+-doped ZnO and their pressure and temperature dependences through high-resolution absorption and emission spectroscopy as a function of Co2+ concentration and their structural conformations as a single crystal, thin film, nanowire, and nanoparticle. Absorption and emission spectra of diluted ZnO:Co2+ (0.01 mol %) can be related to the 4T1(P) → 4A2(F) transition of CoO4 (T d ), contrary to MgAl2O4:Co2+ and ZnAl2O4:Co2+ spine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 54 publications
1
23
0
Order By: Relevance
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 9 However, contrasting results were obtained when these doped Pd(0) nanostructures were treated for selenization using a similar method to that followed for the undoped metal. It was observed that hollow cubic shaped Ag doped Pd 17 (Table S1). Hence, it can be speculated that following selenization of the doped metal, the shape changes but the phase of the final structure is the same as that of the undoped structure.…”
Section: Figures 3a and S4amentioning
confidence: 99%
See 2 more Smart Citations
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 9 However, contrasting results were obtained when these doped Pd(0) nanostructures were treated for selenization using a similar method to that followed for the undoped metal. It was observed that hollow cubic shaped Ag doped Pd 17 (Table S1). Hence, it can be speculated that following selenization of the doped metal, the shape changes but the phase of the final structure is the same as that of the undoped structure.…”
Section: Figures 3a and S4amentioning
confidence: 99%
“…Many studies have been conducted on the doping of a wide variety of inorganic dopants into various metal oxide and semiconductor host nanomaterials and the properties of the newly formed materials have been well studied. 1-9, [14][15][16][17][18][19][20][21][22][23][24][25][26][27] Optically active dopants can create new electronic states and can assist in the creation of new optical centers to produce different colored emissions. 1-8, [14][15][16][17][28][29][30] Similarly, magnetic dopants can even introduce magnetic properties in non-magnetic hosts.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…TiO 2 and ZnO nanoparticles (Z-COTE®) were commercial (BASF Chemical Company). ZnO:Co 2+ nanowires were synthesised in-house [34][35][36]. Chemically exfoliated graphene oxide (GO) was purchased commercially (Graphenea, Spain).…”
Section: Methodsmentioning
confidence: 99%
“…The way these absorption bands contribute to photovoltaic and photoconductivity effects is a critical issue for the above referred applications and has been the object of several studies. 18,33−36 High-pressure techniques are well suited to investigate the electronic structure of semiconductor materials 37 already been used to study the electronic structure of Zn 1−x Co x O NPs, 38 thin films, 35,39−41 and single crystals. 4,42 High pressure was also crucial to elucidate electronic structure effects related to quantum confinement in quantum dots.…”
mentioning
confidence: 99%